Curvilinear relationship between burnout and work engagement among staff in community services for the elderly: A correlation study - Yang, Guangmei; Wei, Huiyan; Wan, Leping; Dong, Haiying; Liang, Xiaoxiao; He, Yan (Frontiers in Public Health, 2022)
Objective: To investigate whether there is a curvilinear relationship between burnout and work engagement among staff in Chinese community services for the elderly. Methods: A stratified whole-group random sampling method was used to survey 244 staff members from eight communities in two cities. Data were collected using the Maslach Burnout Inventory scale (MBI) and the Utrecht Work Engagement Scale- 9 (UWES- 9). The curve estimation method was used to explore the functional model of burnout and work engagement scales. Results: Burnout, Depersonalization(DP), and Personal Accomplishment(PA) were found to be related to work engagement in a cubic function (R2=0.166, P<0.05)、 (R2=0.061, P<0.05) and (R2=0.2230, P<0.05), respectively. There was no statistically significant relationship between Emotional Exhaustion (EE) and work engagement (P>0.05). Conclusions: There was a cubic function relationship between burnout and work engagement, "Personal Accomplishment " was related to work engagement in an inverted U-shaped curve. After reaching a certain level, all three were negatively correlated with work engagement. Therefore, agency heads should recognize the different levels of burnout and the impact of each dimension on work engagement to take targeted measures to alleviate burnout and improve work engagement.